2011
DOI: 10.3174/ajnr.a2680
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Intracranial Aneurysms: New and Enlarging Aneurysms after Index Aneurysm Treatment or Observation

Abstract: BACKGROUND AND PURPOSE:Children with brain aneurysms may be at higher risk than adults to develop new or enlarging aneurysms in a relatively short time. We sought to identify comorbidities and angiographic features in children that predict new aneurysm formation or enlargement of untreated aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 24 publications
1
22
0
2
Order By: Relevance
“…[1][2][3] Aneurysms in the first 2 decades of life comprise about 1% to 4% of all intracranial aneurysms. [4][5][6][7] Long-term angiographic follow-up studies in pediatric intracranial aneurysm patients with mean follow-up times of only 4 to 6 years 5,8,9 show de novo aneurysm formation rates of 13% to 23%. 4,5,9 We gathered data on long-term clinical and angiographic follow-up studies of pediatric aneurysm patients in a singlecenter consecutive series.…”
mentioning
confidence: 99%
“…[1][2][3] Aneurysms in the first 2 decades of life comprise about 1% to 4% of all intracranial aneurysms. [4][5][6][7] Long-term angiographic follow-up studies in pediatric intracranial aneurysm patients with mean follow-up times of only 4 to 6 years 5,8,9 show de novo aneurysm formation rates of 13% to 23%. 4,5,9 We gathered data on long-term clinical and angiographic follow-up studies of pediatric aneurysm patients in a singlecenter consecutive series.…”
mentioning
confidence: 99%
“…There is no consensus on how often or for how long pediatric aneurysm patients should be followed after acute-phase treatment. Recurrence of aneurysm and the development of de novo aneurysms after the initial procedure have been reported in pediatric cases, and these phenomena are highly likely to be related to dissection or fusiform morphology 32,34 . The incidence of recurrent and de novo aneurysms was reported by Kakarla et al to be 2.6% and 7.8% over a mean follow-up duration of 53 months 32 , and Hetts et al reported that 8.4% developed de novo or enlarging aneurysms an average of 4.2 tively because of unavoidable circumstances, it is important to know in which period spontaneous thrombosis can occur and what will happen afterwards.…”
Section: Discussionmentioning
confidence: 99%
“…Careful neuroradiological surveys are needed for pediatric dissecting aneurysms treated endovascularly. years after initial presentation 34 . Moreover, Sanai et al reported that aneurysm recurrence or the development of de novo aneurysms was frequent in children treated endovascularly during a mean follow-up period of 5.7 years 31 .…”
Section: Discussionmentioning
confidence: 99%
“…3 Pediatric cerebral aneurysms are also more frequently giant, tend to form in the posterior circulation and at the internal carotid artery bifurcation, and have a male preponderance. 19,26,30,33 Fusiform aneurysms are less common in adults, more common in children, 6,11 and frequently occur along the MCA branches. 6 The featured case represents a rare saccular aneurysm arising from the inferior division of M 2 with de novo saccular aneurysm formation at the superior division of M 2 .…”
Section: Epidemiology and Natural Historymentioning
confidence: 99%
“…1,13,14,20,30,34,37 The rate of new SAH is higher in both adults and children with a previous aneurysm rupture than in the general population; it occurs as a result of recurrent aneurysms as well as de novo aneurysm formation. 4,35,39 In pediatric patients with a mean follow-up of 4-6 years, 11,15,30 a 13%-23% cumulative rate of de novo aneurysm formation has been reported. 15,29,30 We discuss the case of a 6-month-old girl who initially presented with a ruptured left middle cerebral artery (MCA) aneurysm treated with microsurgical clip ligation who had de novo aneurysm formation and rupture from an adjacent segment just 55 days later and was found to have a mutation in the myosin heavy chain 11, smooth muscle gene (MYH11).…”
mentioning
confidence: 99%